Crystal phase-based epitaxial growth of hybrid noble metal nanostructures on 4H/fcc Au nanowires - Lu, Qipeng (2020)
Crystal-phase engineering offers opportunities for the rational design and synthesis of noble metal nanomaterials with unusual crystal phases that normally do not exist in bulk materials. However, it remains a challenge to use these materials as seeds to construct heterometallic nanostructures with desired crystal phases and morphologies for promising applications such as catalysis. Here, we report a strategy for the synthesis of binary and ternary hybrid noble metal nanostructures. Our synthesized crystal-phase heterostructured 4H/fcc Au nanowires enable the epitaxial growth of Ru nanorods on the 4H phase and fcc-twin boundary in Au nanowires, resulting in hybrid Au-Ru nanowires. Moreover, the method can be extended to the epitaxial growth of Rh, Ru-Rh and Ru-Pt nanorods on the 4H/fcc Au nanowires to form unique hybrid nanowires. Importantly, the Au-Ru hybrid nanowires with tunable compositions exhibit excellent electrocatalytic performance towards the hydrogen evolution reaction in alkaline media.